Synthesis, characterization and antimicrobial studies on Mn(II), Fe(II), Co(II) complexes of schiff base derived from 3-Formylchromone and Benzohydrazide - Hussaina, Aminu Ibrahim; Habu, Nuhu Aliyu; Musa, Husaini; Aysha, Salees Dayyib (جامعة الوادي - university of el oued, 2021)
Schiff base formed by condensation of 3-formylchromone and benzohyrazide and its metal(II) complexes of Mn(II), Fe(II), and Co(II), have been prepared and characterized by conductivity measurement, magnetic susceptibility, IR Spectra, atomic absorption spectroscopy, elemental analysis, as well as melting point/decomposition temperature and solubility test. The melting point of the Schiff base (165 0C) and decomposition temperatures of the complexes (185-198)0C indicating their thermal stability. The molar conductivity measurement determined are in the range (10.54-23.10) Ω-1cm2mol-1 revealing that all the complexes are non-electrolytic in nature. IR spectra of the Schiff base showed a band at 1633cm-1 which assigned to ʋ(-C=N-) stretching vibration. This band was observed downfield in the range (1603 -1655) cm-1 in the spectra of the metal(II) complexes revealing that the Schiff base formed metal complexes with the metal ions. The gram magnetic susceptibility measurements of the complexes showed that all the complexes except that of Zinc are paramagnetic and have tetrahedral geometry. The elemental analysis suggested a metal to ligand ratio of 1:1. The Schiff base and its metal complexes have been screened for their antimicrobial activity against four pathogens. Some compounds were active, while others are not active against the isolates
Article
Keywords: Schiff base; Metal complexes; Synthesis, characterization; Antimicrobial activity; Antifungal activity